2005
DOI: 10.1007/s00268-005-7724-1
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthesia for Surgery Influences Melatonin and Cortisol Levels

Abstract: The purpose of this study was to investigate the effect of general anesthesia and surgery on melatonin production, and to assess the relationship between melatonin secretion and cortisol levels. Twenty (9 males and 11 females) consecutive otherwise healthy patients aged 27 to 52 years were included in this study. The patients underwent laparoscopic cholecystectomy or laparoscopic hernioplasty. All patients had general anesthesia with the same anesthetic drugs. Serum cortisol levels were measured at several tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 57 publications
(46 reference statements)
3
31
1
1
Order By: Relevance
“…Hemodynamic changes are usually unpredictable [27]. Cortisol level is widely used as the marker of surgical stress response [28]. A dose-dependent decrease in heart rate and arterial blood pressure occurred with dexmedetomidine, and decrease of sympathetic nervous activity was observed through the recorded levels of norepinephrine in plasma [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic changes are usually unpredictable [27]. Cortisol level is widely used as the marker of surgical stress response [28]. A dose-dependent decrease in heart rate and arterial blood pressure occurred with dexmedetomidine, and decrease of sympathetic nervous activity was observed through the recorded levels of norepinephrine in plasma [29].…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, melatonin secretion has shown to be acutely disturbed37 with a delay of secretion and reduced amplitude 38 39. Various lines of evidence show that depressed patients exhibit disturbances in both the amplitude and the shape of the melatonin secretion rhythm, with some studies showing a low nocturnal melatonin secretion and others showing an increase in secretion 35.…”
Section: Methodsmentioning
confidence: 99%
“…Because anesthesia is not uncoupled from surgery, it is difficult to separate the effects of general anesthetics from the effects related to, for example, pain, surgical stress, tissue injury, post-operatively administered medications, and hospital stay conditions (Paul & Lemmer, 2007). Though some studies (e.g., Karkela et al, 2002;Ram et al, 2005) suggest that general anesthesia could result in a desynchronization of the circadian time structure, none of these studies documented this aspect. Internal desynchronization is defined as a state in which the circadian period (t) of a set of rhythms differs from 24 h (Reinberg et al, 2007), resulting in an alteration of the normal phase relationships between rhythms, which in turn may give rise to a number of atypical clinical signs, such as fatigue, sleep disorders, and mood alteration.…”
Section: Circadian Rhythms and General Anesthesiamentioning
confidence: 99%
“…Indeed, it was shown by Turkistani et al (2007) that an oral (3 mg) dose of melatonin, as a pre-medication, reduced the dose of propofol required to induce anesthesia, without prolongation of the post-operative recovery room stay. Two studies (Karkela et al, 2002;Ram et al, 2005) using thiopentalisoflurane-fentanyl for morning orthopaedic and laparoscopy surgeries, respectively, showed that serum and salivary melatonin levels decreased the first night after anesthesia and did not regain the basal secretion level until 48 h or longer. Cronin et al (2000) also demonstrated that general anesthesia by inhalation (anesthetic unspecified) conducted in conjunction with a gynecology surgical procedure decreased nocturnal melatonin concentration the night following intervention compared to the second and third post-operative nights, with the decrease amounting to 350% between the first and third nights; melatonin secretion returned to basal values only after the third night.…”
Section: General Anesthesia and Melatoninmentioning
confidence: 99%